Gesellschaftsrecht und Verbraucherschutz - Zum Widerruf von Fondsbeteiligungen. Vortrag, gehalten vor der Juristischen Gesellschaft zu Berlin am 29. September 2004 - Armbrüster, Christian (Schriftenreihe der Juristischen Gesellschaft zu Berlin, 2005)
This volume is a written version of a lecture given to the Berlin Legal Society. The text deals with the relationship between Company law and Consumer Protection law in the field of capital investments. Several questions concerning this matter have recently been highly controversial before German courts. The main issue is whether an investor who exercises the right to revoke his accession to an investment company is thus able to withdraw his initial share independent of the present value of his holding.